Methylation-Specific PCR Unraveled - Sarah Derks; Marjolein H. F. M. Lentjes; Debby M. E. I. Hellebrekers; Adriaan P. de Bruïne; James G. Herman; Manon van Engeland (Cellular Oncology)
Methylation‐specific PCR (MSP) is a simple, quick and cost‐effective method to analyze the DNA methylation status of virtually any group of CpG sites within a CpG island. The technique comprises two parts: (1) sodium bisulfite conversion of unmethylated cytosine's to uracil under conditions whereby methylated cytosines remains unchanged and (2) detection of the bisulfite induced sequence differences by PCR using specific primer sets for both unmethylated and methylated DNA. This review discusses the critical parameters of MSP and presents an overview of the available MSP variants and the (clinical) applications.